An immunoresponsive three-dimensional urine-tolerant human urothelial model to study urinary tract infection - Jafari, Nazila V.; Rohn, Jennifer L. (Frontiers in Cellular and Infection Microbiology, 2023)
Murine models of urinary tract infection (UTI) have significantly improved our understanding of host-pathogen interactions. However, given some key differences between the rodent and human bladder which may modulate host and bacterial response, including certain biomarkers, urothelial thickness and the concentration of urine, the development of new human-based models is important to complement mouse studies and to provide a more complete picture of UTI in patients. We originally developed a human urothelial three-dimensional (3D) model which was urine tolerant and demonstrated several biomarkers of the urothelium, but it only achieved human thickness in heterogenous, multi-layered zones and did not demonstrate the comprehensive differentiation status needed to achieve barrier function. Here, we report an improved 3D urine-tolerant human urothelial model (3D-UHU), which after 18-20 days of growth, stratifies uniformly to 7-8 layers. We confirmed by flow-cytometric analysis that the model is comprised of the three expected, distinct human cell types. The apical surface differentiated into large, CD227+ umbrella-like cells expressing uroplakin-1A, II, III, and cytokeratin 20, all of which are important terminal differentiation markers, and a glycosaminoglycan layer. Below this layer, several layers of intermediate cells were present, with a single underlying layer of CD271+ basal cells. The apical surface also expressed E-cadherin, ZO-1, claudin-1 and -3, necessary for barrier formation; barrier integrity was confirmed by transepithelial electrical resistance and FITC-dextran permeability assay. Infection with both Gram-negative and Gram-positive bacterial classes elicited elevated levels of pro-inflammatory cytokines and chemokines characteristic of urinary tract infection in humans, and caused a decrease in barrier function, suggesting that the 3D-UHU model holds promise for studying host-pathogen interactions and host urothelial immune response.